Penyebab Pending dan Dispute Klaim Kasus Covid-19 Di Rumah Sakit Tipe C dan D Jawa Tengah - Khamna Diah Oktavia Chalimah; Sutrisno Sutrisno; Umi Hanik; Umi Maftukhah; Suyoko Suyoko; Faik Agiwahyuanto; Deddy Setiadi (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
Return of claims for cost of treating COVID-19 patients from BPJS Health is common occurrence due to administrative and service problems. In 2021, there were 215 pending files and 32 unapproved files in type C and D hospitals in Central Java. To determine causes of pending and disputed COVID-19 cases in type C and D hospitals in Central Java. Methods: Descriptive research was conducted by observing all pending and dispute files of COVID-19 cases, totaling 247 cases in 2021. Data collection method was documentation. Univariate data analysis. Panti Wilasa Dr. Cipto Semarang Hospital has highest pending claims for COVID-19 cases. Kelet Jepara Hospital has pending claims for most COVID-19 cases. Majority of pending claims for COVID-19 cases do not have supporting files or are not appropriate, while smallest scanned laboratory results (albumin, PCR) are not attached, and INA-CBGs entry or exit date does not match the medical resume. Most pending and dispute claims for COVID-19 cases are mismatch of diagnosis and diagnostic results with KMK Technical Guidelines, while mismatch of diagnosis with results of actions is least.